The Role of Managed ETL Platforms in Reducing Data Integration Time and Improving User Satisfaction - Gupta, Alok; Selvaraj, Prassanna; Singh, Ravi Kumar; Vaidya, Harsh; Nayani, Aravind Reddy (Journal for Research in Applied Sciences and Biotechnology, 2022)
Managed ETL (Extract, Transform, and Load) solutions are essential for enhancing data acquisition that enhances the user’s satisfaction. By automation and optimizing data activities of these systems, integration times are saved and there is an enhancement of system stability noticed. It also outlines how multiple ETL approaches are discussed with consideration of comprehensive criteria that involves the clarity of a method, its scaling capabilities, user-friendliness, and performance in real-life scenarios. The results revealed that the managed ETL systems have a higher operational experience, but it faces challenges such as integration and usability issues. There is still a need to focus on the optimization of the future development of ETL systems, other performance factors, and the characteristics of the industry for the future enhancement of the existing problems.